KARAKTERISTIK PASIEN TUBERKULOSIS PARU DENGAN MULTIDRUG-RESISTANT (TB MDR) DI RSUD DR. M. HAULUSSY AMBON TAHUN 2014-2018 - Nadhirrafie Ardiadi Albaihaqi; Burhanuddin Burhanuddin; Vina Z. Latuconsina (Fakultas Kedokteran Universitas Pattimura, 2020)
Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis. The last few decades emerged another problem related to tuberculosis namely MDR TB (Tuberculosis with multidrug-resistant) which is very widespread. MDR TB treatment takes 2 years and with drugs that are 100 times more expensive when compared to first-line treatment. The purpose of this research was to determine the characteristics of multidrug-resistant pulmonary tuberculosis patients (MDR TB) in Dr. M. Haulussy Ambon in 2014 - 2018. This research is an observational descriptive research with cross sectional approach. The sampling technique is to use the total sampling method. The sample in this research amounted to 113 people. MDR TB patient medical record data obtained were then analyzed using Microsoft Excel. The results of the research showed that in RSUD Dr. M. Haulussy Ambon, MDR TB sufferers were mostly found in adulthood 26 - 45 years, namely 61 cases (54%), MDR TB patients were male, 69 cases (61%), type of patient relapsed 67 cases (59% ), 39 cases (34.51%) with duration of treatment 0 - 5, rifampicin-resistant patients were 79 cases (69.9%), patients died as many as 32 cases (28.3%) and there were 8 cases (7.1 %) MDR TB p atients are HIV positive.